Visits to the Client when Tendering for Consulting Contracts: Sourcing Information or Influencing the Client? - Roger Svensson (The Research Institute of Industrial Economics (IUI), 2000)
Consulting firms (CFs) sell services on a project basis to many clients and must therefore continuously tender for new contracts. One frequently used strategy by CFs is to visit the clients in connection to the tenders. The reason to the visits is either: 1) to influence the client in his decision-making in some sense; or 2) to source information about the project so that a better proposal can be submitted. Using a unique database on individual proposals, I examine empirically which of these two reasons is the most important. The estimations suggest that influencing the client dominates as explanation to the visits.
Keywords: F23; L14; L84; M31; 330; Consulting services; Procurement; Visits; Information sourcing; Lobbying; Marketing; Unternehmensberatung; Vertrag; Strategisches Management; Theorie